The Anglo-Saxon Preference toward High-rise Buildings inspired by Italian Medieval Towers between the 19th and 20th Centuries - Kawamura, Ewa (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2021)
Between the 19th and 20th centuries, the architecture of city halls often chose to incorporate a tower, as a symbol of administrative power, while towers of commercial buildings indicated financial power. Fire stations had a tower suitable for watching over the city and railway stations or universities had clock towers. Anglo-Saxon architects designed towers inspired by Italian medieval examples, while many British shafts and chimneys imitated Italian bell towers and the first American skyscrapers were also inspired by the aforementioned Italian towers.